PEMBAURAN CAKRAWALA YANG MENTRANSFORMASI HIDUP DALAM PEMBUKAAN SURAT PAULUS KEPADA JEMAAT GALATIA (GAL 1:11-24) - R.F. Bhanu Viktorahadi (Litbang STFT Widya Sasana Malang, 2018)
Paul wanted to affirm that his life transformations were not only caused by humane influence, but by his personal encounters with Jesus. His personal experience has became an authoritative power that no one could deny because of its authentic and personal nature. His personal experience with Christ became the basis of Paul’s personal transformation, from a persecutor of Christ’s into a defender of Christ’s banners. His expression of his life and faith experience which he shared with his readers and audience were fruitful. Because of his shared life experience, the horizon diffusion became common incidents. The diffusion was possible and would resulted in personal-existential life transformations if there were some courage to dialogue. Growing courage to dialogue was the form of repentance for Church, just like Paul who had to exit from his well-mastered understanding of Jews tradition and enter the mind of Greece to preach Christ. Eventually, in this context, repentance was not only demanded from local societies, but also from Church, because even in a true climate of openness and freedom, many religion followers did not have the courage to find and meet their fellow believers, moreover among societies that were having racial or religious conflict. Paulus ingin menegaskan bahwa transformasi hidupnya tidak hanya disebabkan oleh pengaruh manusiawi, tetapi juga oleh perjumpaan pribadinya dengan Yesus. Pengalaman pribadinya telah menjadi kekuatan otoritatif yang tidak dapat disangkal oleh siapa pun karena sifatnya yang otentik dan pribadi. Pengalaman pribadinya dengan Kristus menjadi dasar transformasi pribadi Paulus, dari seorang penganiaya Kristus menjadi pembela Kristus. Ekspresi hidup dan keyakinannya yang ia bagikan dengan para pembaca dan pendengarnya telah menghasilkan buah. Karena pengalaman hidup yang dibagikannya tersebut, pembauran cakrawala menjadi pengalaman semua. Pembauran cakrawala itu telah menjadi mungkin dan menghasilkan transformasi personal-eksistensial karena ada keberanian untuk berdialog. Tumbuhnya keberanian untuk berdialog telah membentuk pertobatan bagi Gereja, sama seperti Paulus yang harus keluar dari pemahamannya yang sangat menguasai tradisi Yahudi dan memasuki pikiran Yunani untuk mewartakan Kristus. Akhirnya, dalam konteks ini, pertobatan tidak hanya dituntut dari masyarakat setempat, tetapi juga dari Gereja, karena bahkan dalam iklim keterbukaan dan kebebasan yang, banyak pengikut agama tidak memiliki keberanian untuk menemukan dan berjumpa dengan rekan seiman mereka, terlebih di tengah masyarakat yang mengalami konflik ras atau agama